Financial policies and the aggregate productivity of the capital stock: evidence from developed and developing economies - Philip Arestis; Panicos Demetriades; Bassam Fattouh (Levy Economics Institute of Bard College, 2002)
We collect data on a number of financial restraints, including restrictions on interest rates and capital flows and reserve and liquidity requirements, and capital adequacy requirements from central banks of 14 countries. We estimate the effects of these policies on the aggregate productivity of the capital stock, controlling for the effects of inputs and financial development and using modern econometric techniques. We find that financial development has positive effects on productivity, while the effects of financial policies vary considerably across countries. Our findings demonstrate that financial liberalization is a much more complex process than has been assumed by earlier literature, and its effects on macroeconomic aggregates are ambiguous.
Keywords: 330